Azilsartan medoxomil in the treatment of hypertension: the definitive angiotensin receptor blocker?. (November 2013) - Barrios, Vivencio; Escobar, Carlos
Abstract : Introduction: Azilsartan medoxomil is the newest angiotensin receptor blocker marketed for the treatment of arterial hypertension. The aim of this article was to review the available evidence about this drug alone or combined with other antihypertensive agents in the treatment of hypertensive population. Areas covered: For this purpose, a search on MEDLINE and EMBASE databases was performed. The MEDLINE and EMBASE search included both medical subject headings (MeSHs) and keywords including azilsartan or azilsartan medoxomil or angiotensin receptor blockers or renin angiotensin system or chlorthalidone and hypertension. References of the retrieved articles were also screened for additional studies. There were no language restrictions. Expert opinion: Azilsartan medoxomil has a potent and persistent ability to inhibit binding of angiotensin II to AT1 receptors, which may play a role in its superior blood pressure (BP) -lowering efficacy compared with other drugs, including ramipril, candesartan, valsartan or olmesartan, without an increase of side effects. Chlortalidone is a diuretic which significantly differs from other classic thiazides and has largely demonstrated clinical benefits in outcome trials. The fixed-dose combination of azilsartan and chlorthalidone has been shown to be more effective than other potent combinations of angiotensin receptor blockers plus hydrochlorothiazide, with a good tolerability profile.